Is it time for a world currency? - Rasul Shams (Hamburg Institute of International Economics (HWWA), 2002)
There have been several proposals to reduce the observed volatility of flexible exchange rates. The paper reviews two recent opposite views on the appropriateness of a common world currency for this purpose. Referring to an adequately formulated theory of world money, it is shown that there is presently no alternative to a flexible exchange rate system. This system might, under specific conditions, gradually evolve into a world monetary system with a global currency. Developing some structural principles of the world economy the paper also explains some hitherto unexplained features in the development of international monetary relations. – – Es existieren viele Vorschläge zur Reduktion der hohen Volatilität flexibler Wechselkurse. Im Papier werden zwei neuere, einander ausschließende Ansichten über die Angemessenheit einer Weltwährung zu diesem Zweck diskutiert. Auf Grundlage einer adäquat formulierten Theorie internationaler Währungen wird gezeigt, daß gegenwärtig keine Alternative zu einem flexiblen Wechselkurssystem besteht. Auf lange Sicht dagegen könnte jedoch zur Entstehung eines Währungssystem mit einer einzigen internationalen Währung kommen. Darüber hinaus werden einige weltwirtschaftliche Strukturprinzipien formuliert, die dazu dienen, einige bisher unverstanden gebliebene Entwicklungen in den internationalen Währungsbeziehungen zu erklären.
Keywords: F; F3; F33; 330; World Money; International Transactions; National Currencies as International Monies; Credit Money; Multi-currency Standard; Internationales Währungssystem; Währungsunion; Flexibler Wechselkurs; Weltwirtschaftspolitik; Welt